What's in the Literature?. Issue 4 (June 2016) - Silvestri, Nicholas J.; Wolfe, Gil I.; Bromberg, Mark; Lacomis, David
Abstract : Abstract: One of the first questions asked by patients and family members when a diagnosis of amyotrophic lateral sclerosis is made is "what about stem cells?" The term "stem cells" has attractiveness to it, with the assumption that stem cell treatment (stem nerve cells) can replace lost nerve cells. There are perhaps 2 types of stem cell trials, those that are vetted by the Food and Drug Administration and those that have no official oversight and whose results are infrequently published. The issue of the latter was discussed in the last edition of this column. The results of one of the formal stem cell trials now in the United States have been reported. Spinal muscular atrophy is a form of motor neuron disease affecting children and has a genetic cause, which has led to a feasibility study giving antisense oligonucleotides, and the results have also been reported. Biomarkers of amyotrophic lateral sclerosis are being sought, and the presence of neurofilaments is promising. Inflammatory neuropathies are an important group because they are treatable. Intravenous immune globulin is a commonly used agent, but a number of questions persist: one is efficacy among brands, another is the probability of a response, and a third is optimum dosing and taper schedules. A number of recent articles address these issues. The predictive value of single-fiber electromyography in determining which patients with ocular myasthenia will develop generalized disease, the risk of crisis after thymectomy, and 2 papers discussing new forms of congenital myasthenic syndrome are discussed. The risk of brain tumors, quality of life, and the assessment of trunk muscle strength in patients with type 1 myotonic dystrophy is reviewed. An article describing the discovery of mutations in SCN4A as a cause of congenital myopathy is discussed, as is one describing the occurrence of rhabdomyolysis in a group of patients subsequently discovered to have various forms of muscular dystrophy. Finally, articles describing the features of patients with inflammatory myopathies and Jo-1 and either 3-hydroxy-3-methylglutaryl-conezymea reductase or to signal recognition particle antibodies are reviewed.